Taxation, innovation and the environment - Ash, Michael; Organisation for Economic Co-operation and Development ([Paris] OECD, 2010)
"OECD governments are increasingly using environmentally related taxes because they are typically one of the most effective policy tools available. Exploring the relationship between environmentally related taxation and innovation is critical to understanding the full impacts of this policy instrument as well as one potential facet of 'green growth'. By putting a price on pollution, do environmentally related taxes spur innovation? What types of innovation result? Does the design of the tax play a critical role? What is the effect of this innovation? In analyzing these questions, this report draws on case studies that cover Japan, Korea, Spain, Sweden, Switzerland, the United Kingdom, Israel and others. It covers a wide set of environmental issues and technologies, as well as the economic and policy contexts. The research methods range from econometric analysis to interviews with business owners and executives. The report also explores the use of environmentally related taxes in OECD countries and outlines considerations for policymakers when implementing these taxes."--Publisher's description.
Introduction -- Current use of environmentally related taxation -- Effectiveness of environmentally related taxation on innovation -- Tax design considerations and other tax-based instruments -- A guide to environmentally related taxation for policy makers -- Annexes : A. Sweden's charge on NO[subscript x] emissions -- B. Water pricing in Israel -- C. Cross-country fuel taxes and vehicle emission standards -- D. Switzerland's tax on volatile organic compounds -- E. R&D and environmental investments tax credits in Spain -- F. Korea's emission trading system for NO[subscript x] and SO[subscript x] -- G. UK firms' innovation responses to public incentives : an interview-based approach -- H. The UK's climate change levy and climate change agreements : an economic approach -- I. Japan's tax on SO[subscript x] emissions. -- Current use of environmentally related taxation -- Effectiveness of environmentally related taxation on innovation -- Tax design considerations and other tax-based instruments -- A guide to environmentally related taxation for policy makers.
Also available in French: La fiscalitâe, l'innovation et l'environnement.
Keywords: Environmental impact charges; Taxation -- Environmental aspects; Environmental protection -- Technological innovations -- Taxation; Technological innovations -- Environmental aspects -- Taxation